Comparison of Seismic Performance Levels of Five-Story Limited Ductility and Confined Masonry Structures, Lima, Perú - Bendezu Romero, Lenin Miguel (2025)
This study evaluates the seismic behavior of a five-story multifamily building by comparing two structural systems: Limited Ductility Walls (LDW) and Confined Masonry Walls (CMW). The structural models were developed using Estera 3D software, and the analysis was carried out exclusively through nonlinear static analysis (pushover). Four levels of seismic demand were considered: frequent, occasional, design, and maximum earthquakes. Both systems achieved the same structural performance levels according to code-based criteria: full operation for the frequent earthquake; operation with minor damage for the occasional and design earthquakes; and life safety for the maximum earthquake. However, quantitative results show better performance for the LDW system. For the design earthquake, the LDW system exhibited a maximum base shear of 1141.36 tons and a top-level displacement of 7.098 cm, while the CMW system reached 2371.63 tons and 2.9696 cm, respectively. In terms of spectral acceleration, LDW registered 935.20 gal compared to 1098 gal for CMW. For the maximum earthquake, the LDW system reached a displacement of 10.68 cm and a base shear of 1272.15 tons, whereas the CMW system reached 8.0686 cm and 2291.71 tons. These results indicate that, although both systems meet the established performance objectives, the LDW system demonstrates more efficient structural behavior and greater energy dissipation capacity under severe seismic events.